Analisis trend harga ayam broiler di masa pandemi covid-19 di Sulawesi Selatan: Trend of broiler pricesi n South Sulawesi during covid-19 pandemic - Aslina Asnawi; Muhammad A. Akbar; Siti Nurlalelah (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2023)
The Covid-19 pandemic has had an impact on all sectors, including the broiler farming sub-sector, both at the farmer level and at the marketer level. This study aims to determine trends in chicken prices and analyze the factors that influence chicken prices during the Covid-19 pandemic. This research was conducted April - May 2021 in South Sulawesi. The type of research used descriptive quantitative research. Data collection uses documentation method related chicken price data obtained from Indonesian People's Poultry Association (PINSAR) and direct interviews with PINSAR Chair of South Sulawesi. Data analysis used is descriptive analysis, qualitative analysis and time series forecasting methods, namely the moving average method and least square. The results showed that trend of chicken prices in 2020 fluctuated. Chicken prices in January-March 2020 fluctuated but were relatively controlled. The highest prices are in June until of December are very volatile. The factor that causes changes chicken prices the government's policy form of Large-Scale Social Restrictions so that many business sectors must be closed such as supply centers, restaurants, and others, causing difficulties in chicken distribution. The right forecasting method forecasting chicken prices moving average method because forecast value produced has relatively lower error rate than least square method.